Study of Diet Variations According to Patient Nutrition Needs on SF Hospital Nutrition Instalation. - Rahmah Utami Budiandari; Al Machfud WDP; Mariah Alqibtiyah (Journal of Halal Lifestyle and Sustainability, 2025)
This article aims to determine the composition and diet variation according to patients nutritional needs at SF Hospital.  The methodology used was observation, interviews with nutrition staff, literature review, and qualitative data analysis. This article shows that different menus served every day,  tailored to the nutritional needs of consumers. The diet menu is tailored to each patient's energy needs to optimize the recovery process. Dietary food choices are also based on the patient's age, daily activity level, gender, and medical history